T lymphocytes bearing complement receptors in a patient with chronic lymphocytic leukaemia. - Toben, H R (1977)
A patient is described who presented with a disease clinically resembling chronic lymphocytic leukaemia, characterized by generalized lymphadenopathy, pleural and peritoneal effusions, a blood lymphocyte count of 700,000/mul and failure to respond to conventional therapy. At least 95% of these cells formed rosettes with sheep erythrocytes (E) and with erythrocytes coated with 19S antibodies and complement (EAC). All of these cells bound rabbit anti-human thymocyte serum; this serum bound to 0--22% of the lymphocytes from twenty other patients with chronic lymphocytic leukaemia. These unusual cells did not bear surface immunoglobulin detectable by immunofluorescence. The clinical and cellular features of this malignancy are compared to previously reported cases of T cell chronic lymphocytic leukaemia. As this case illustrates, T-cell chronic lymphocytic leukaemia may present without skin lesions and may be a more aggressive disease than the more common B-cell neoplasm.